Social Media Usage by Marketing Academics in Poland - Empirical Research - Mazurek , Grzegorz (Studia Oeconomica Posnaniensia, 2017)
Social media are interactive means of communicating, collaborating and sharing information in virtual environments. The on-going universal phenomenon of social media raises questions about whether and how they should be applied in HEIs. This article discusses the results of a survey conducted on a sample of 169 research and teaching staff in marketing in Polish higher education institutions. The aim of the study was to identify the scale, scope, objectives and barriers of using social media. In particular, it was about identifying the role of social media in didactic work, communication with students, research work and broadly defined image creation and the popularization of own activities.